Speaker Dependent Voice Controlled Robotic Arm - Akcmar, Doga; Ariturk, Mustafa Kemal; Yildirim, Tulay (IEEE, 2018)
Speech recognition is the ability of a machine or program to identify spoken words on the spoken language and convert them into a machine-readable form. These systems, together with developing technology, are beginning to gain an increasingly important place today. Speech recognition systems are used in a wide range of areas such as security control, remote access to a computer or phone, person recognition without speaking, call center routing, voice dialing. In this paper, it is aimed to integrate the speech recognition system into the robotic arm and accordingly move the robot arm with the voice commands given instantaneously, hold the object and leave it. At the same time, the voice recognition system to be used in this work depends on the person and will only detect the voice of the desired person to make the system more reliable.
Keywords: Computer Science; Engineering